1997
DOI: 10.1161/01.cir.96.2.535
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Measurement of Shortening in the Fiber and Cross-Fiber Directions in the Normal Human Left Ventricle and in Idiopathic Dilated Cardiomyopathy

Abstract: In normal humans, the direction of maximal deformation aligns with the fiber direction in the epicardium but is perpendicular to the fiber direction in the endocardium. When strain in a coordinate system aligned to the fibers is estimated, cross-fiber shortening is found to be the dominant shortening strain at the endocardium. Normal fiber shortening is 15%, and this is markedly reduced in IDC. The normal transition in fiber orientation through the wall is not altered in IDC, and cross-fiber shortening is stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(109 citation statements)
references
References 28 publications
8
101
0
Order By: Relevance
“…22 However, the development of MR myocardial tagging has facilitated the detailed evaluation of abnormalities in regional LV myocardial function not only in the setting of HCM, 2,5 but also in hypertensive heart disease, 4 ischemic heart disease 8 and dilated cardiomyopathy. 9 Three-dimensional MR imaging is a recent development. 7 The refinement of MR SPAMM myocardial tagging is expected to facilitate the understanding of the pathophysiology in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 However, the development of MR myocardial tagging has facilitated the detailed evaluation of abnormalities in regional LV myocardial function not only in the setting of HCM, 2,5 but also in hypertensive heart disease, 4 ischemic heart disease 8 and dilated cardiomyopathy. 9 Three-dimensional MR imaging is a recent development. 7 The refinement of MR SPAMM myocardial tagging is expected to facilitate the understanding of the pathophysiology in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] In particular, the spatial modulation of magnetization (SPAMM) method uses noninvasive recognition of markers for specific myocardial regions for analyzing the myocardial thickening or thinning during the cardiac cycle. 2,5,8 Previous studies have reported that left ventricular (LV) contractility is impaired in the hypertrophied regions in patients with hypertrophic cardiomyopathy (HCM).…”
mentioning
confidence: 99%
“…To obtain LV mass, images were postprocessed using Cardiac Image Processing System, previously used in published studies from our group. 22,23 The endocardial margin was detected visually and contoured manually. The area of the LV cavity in the slice was calculated, and volume was estimated by factoring the known slice thickness, which assumed boundaries that were orthogonal to the imaging plane.…”
Section: Mass By Magnetic Resonance Imagingmentioning
confidence: 99%
“…The new axes were radial (R) using the perpendicular direction to the wall; fiber (F), tangent to the surface and parallel to the local fiber orientation at either the epicardium or endocardium; or cross fiber (X), tangent to the surface and perpendicular to F. Fiber directions were obtained from histological fiber angle data in cadaver studies. [13][14][15] Normal and shear strains were computed from the displacements from end diastole to end systole. Positive radial strains represented wall thickening; negative strains, wall thinning; and negative fiber strains, quantified shortening of the myocardium along the local direction of the actively contracting fibers.…”
Section: Strain Computationsmentioning
confidence: 99%